A Grid Connected Photovoltaic Generation System With Compensation Of Current Harmonics And Voltage Sags - Cavalcanti, Marcelo Cabral; Azevedo, Gustavo Medeiros de Souza; Amaral, Bruno de Aguiar; Neves, Francisco de Assis dos Santos; Moreira, Davi Carvalho; Oliveira, Kleber Carneiro de (Eletrônica de Potência, 2006)
This paper presents a system that provides photovoltaic generation as well as the ability to compensate current harmonics and voltage sags. The system can be controlled for current harmonics and reactive power compensation simultaneously by using a converter operating as shunt active filter. Another converter is used as active series filter and it compensates voltage harmonics and voltage sags and swells. Using only one dc-ac converter in photovoltaic energy conversion process, the system presents increased efficiency when compared to the conventional systems, composed by a dcdc converter and a dc-ac converter. The synchronous reference frame method is used to control the three-phase converters. Simulation results demonstrate the good performance of the proposed configuration. Experimental results corresponding to the operation of the series filter as voltage sag compensator are presented.